Bridge the Gap: Using Challenge-Based Learning to Connect University and Industry - Sanchez, Miguel Ángel; Lamo-Anuarbe, Paula (IEEE Revista Iberoamericana de Tecnologias del Aprendizaje, 2024)
Collaboration between universities and companies has become vital in training future professionals. However, on many occasions, this collaboration could be more agile and efficient to avoid a disconnect between the supply of trained professionals and the demand of the labor market. This situation is aggravated in the case of online training, where students are geographically delocalized and need the opportunity to interact directly with companies. To address this issue and ensure up-to-date and relevant student training, an innovative program that promotes collaboration between the university and various organizations in the Master in Industry 4.0 is presented. The proposal offers a new subject that uses learning based on challenges proposed and directed by leading companies in the sector. This allows students to apply their knowledge and gain insight into the industry in which they will work. Four calls have been carried out, and there are 14 challenges available, covering various industrial sectors and applications related to Industry 4.0/5.0. This paper presents the results of this program. Companies have obtained innovative and valuable solutions for their specific needs. In contrast, students have been able to apply their knowledge in real situations and gain valuable experience in the business world. Many students come from different geographical environments, especially from LATAM, and they value the subject and teaching staff positively. Due to the success of the program in Master in Industry 4.0, the same approach has been implemented in the university’s master’s program in the Internet of Things, with equally satisfactory results.
Keywords: challenge-based learning; Industry 4.0/5.0; digital transformation; university-industry collaboration; online education; project-based learning